Non-chemical water treatment in unified light and sound field and testing on waste water decontamination. (November 2019) - Lebedev, O; Gavrilov, Yu; Timkovskii, A L; Bezrukova, A G; Lezhnev, E I; Polyanskii, V A; Timofeev, A N; Akhmetova, I G
Abstract: The paper presents the results of testing of a high-performance method for decontaminating sewage, involving combination of ultrasonic and ultraviolet exposure at the final step of water purification aimed at destroying pathogenic microorganisms and thereby preventing the spread of infectious diseases. A variation of the method was developed and patented by the authors and passed the test at one of the most advanced water facilities in Russia which is the Vodokanal of St. Petersburg. The combined unit was manufactured at OOO Novotech-EKO and installed at the South-West Wastewater Treatment Plant (SWTP) of Vodokanal of St. Petersburg. The results of the test showed the efficiency of combined ultraviolet and ultrasonic wastewater treatment, both in terms of intensifying disinfection and in terms of the stability of the plant operation by preventing biofouling and salt deposition on the surface of the lamp casings. The latter fact was the basis for the pilot project of improvement of the existing system of UV wastewater disinfection at the SWTP.